Gapless inhomogeneous superfluid phase with spin-dependent disorder - M Jiang; R Nanguneri; N Trivedi; G G Batrouni; R T Scalettar (New Journal of Physics, 2013)
We show that the presence of a spin-dependent random potential in a superconductor or a superfluid atomic gas leads to distinct transitions at which the energy gap and average order parameter vanish, generating an intermediate gapless superfluid phase, in marked contrast to the case of spin-symmetric randomness where no such gapless superfluid phase is seen. By allowing the pairing amplitude to become inhomogeneous, the gapless superconducting phase persists up to considerably higher disorder compared with the prediction of Abrikosov–Gorkov. The low-lying excited states are located predominantly in regions where the pairing amplitude vanishes and coexist with the superfluid regions with a finite pairing. Our results are based on inhomogeneous Bogoliubov–de Gennes mean field theory for a two-dimensional attractive Hubbard model with spin-dependent disorder.